Future Prospects of UAV Tilt Photogrammetry Technology. (October 2019) - Ren, Jinghong; Chen, Xuan; Zheng, Zhangzhe
Abstract: In recent years, China's science and technology have developed rapidly, and the surveying and mapping industry has also made great breakthroughs. Traditional aerospace photogrammetry cannot collect more accurate information from modern surveying and mapping. In recent years, UAV tilt photogrammetry technology has been developed. UAV tilt photogrammetry technology can more realistically reflect the position and appearance of features. Traditional aerospace photogrammetry can only perform vertical data acquisition, but tilt photogrammetry can perform fast and efficient data acquisition from different angles. Not only that, tilt photogrammetry has greatly improved the image matching and measurement technology. This paper analyzes the future development trend and application fields of the development of tilt photogrammetry technology.